Enantio-and diastereoselective desymmetrization of α-alkyl-α-diazoesters by dirhodium(II)-catalyzed intramolecular C–H insertion. Issue 27 (7th July 2016) - Miyazawa, Taku; Minami, Kazushi; Ito, Motoki; Anada, Masahiro; Matsunaga, Shigeki; Hashimoto, Shunichi
Abstract: The first enantio-and diastereoselective construction of fused bicyclic ring systems via intramolecular C–H insertion reaction of σ-symmetric α-alkyl-α-diazoesters is described. With dirhodium(II) tetrakis[ N -phthaloyl-( S )- tert -leucinate], Rh2 ( S -PTTL)4, the C–H insertion proceeded in a chemoselective manner to give methyl bicyclo[3.3.0]oct-7-ene-2-carboxylate and methyl bicyclo[4.3.0]nonane-7-carboxylate derivatives with up to 99% ee and perfect cis diastereoselectivity. The utility of this protocol was demonstrated by the catalytic asymmetric synthesis of a key intermediate in Whitesell's synthesis of udoteatrial hydrate. Graphical abstract: